(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Exports of marine products are important to the Indian economy in terms of employment and income generation, as well as valuable foreign exchange earnings. India is the world’s fourth largest exporter of seafood products, with total export value of USD 6.73 billion, accounting for 4.35 percent of the total global exports. This study analyses the issues and challenges faced by the seafood processing export industries in Kerala. The success of fishery export processing industry can be achieved by minimizing the cost production and improving quality standards to attain higher economies of scale. Seafood processing industries face lot of problems in both demand and supply side issues. However, compliance of Food Safety Standard, QualityIssues, Tariff and Non-Tariff Barriers, Anti-dumping duty and increase in the degree of global level competition are some of the potential treats that must be taken into account by the Seafood export processing industries in Kerala.